Rancang Bangun Aplikasi Penilaian Kinerja Distributor Pupuk Bersubsidi Pada Dinas Pertanian Perkebunan Peternakan Kabupaten Sidoarjo - Budiono, Ari Setyo; Nurcahyawati, Vivine; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Distributors are intermediaries between producers and consumers, distributor role is quite important in the process of distributing goods to consumer needs. Distribution process is well organized, can help develop economy. One of them is subsidized fertilizer, fertilizer production facilities is supporting farmers to determine the achievement of national self-sufficiency in agricultural production. current problems KPPP difficulties in assessing the performance of distributors due process of calculating indicators to distributors are not applied. Consequently monitoring the performance of distributors not inaccurate. The impact of these problems is the KPPP does not determine the development of subsidized fertilizer distribution, if the distributor do action fertilizer distribution irregularities. ( Permendag 15/ M-DAG/PER/4/2013 about procurement and distribution of fertilizer subsidized agricultural sector). Based on these problems, Application a performance assessment distributor use 5 indicators are legality aspect, accessibility aspect, quantity fulfillment aspect, quality fulfillment aspect and respon and lead time aspect. This indicators as a measure to support the fulfillment subsidized fertilizer requirement is right on target. Applications are made to produce performance assessment report, distributors quality report, and distributors level reports. Based on the application made and a series of trials that have been done KPPP can find out the information required in accordance with the purpose of performance appraisal distributor Keywords : Application, Distributors, performance assessment